Intrauterine devices in the conservative treatment of endometrial cancer: progress to date and potential for the future. (July 2011) - Minig, Lucas; Franchi, Dorella; Sideri, Mario
Uterus-sparing hormonal treatment of patients affected by well-differentiated endometrial carcinoma is becoming an important issue. High doses of oral progesterone is the most common drug for treating these patients. However, the levonorgestrel intruterine device has recently been shown to be effective in some patients with a strong desire for future pregnancies or with high surgical risk. Local administration of the hormone therapy, moreover, can avoid the most frequent adverse side effects caused by oral progesterone. Patient selection to exclude preexisting myoinvasive or distant disease is a crucial, although imperfect, prerequisite. Given the risks of disease progression or relapse, close follow-up during and after treatment to monitor failures is crucial. Therefore, in this article we review the current evidence regarding the efficacy of the levonorgestrel-intrauterine device for treating well-differentiated endometrial carcinoma limited to the endometrium.